Distributed dynamic mobility management scheme for network mobility - Wagan, A.A. (EAI, 2017)
Various network management research communities have developed mobility management solutions for the Network Mobility Basic Support Protocol (NEMO-BSP) to allow seamless attachment between heterogeneous networks. The mobility management is the mobility solution dealing with a node's location update and its data delivery. NEMO is a host-based scheme that is still facing QoS issues. Whereas, the network-based mobility schemes have significantly reduce the involvement of the host in the node mobility tasks, but due to the centralized entity approach this scheme is considered less scalable. The Distributed Mobility Management (DMM) scheme is more scalable and aims to alleviate the traditional network mobility management schemes. In this paper, we propose a new DDMM scheme, which is aimed to reduce the tunneling cost and the overall packet delivery cost by implementing the Distributed Local Fix Routers (DLFRs). The results obtained demonstrate that the suggested DDMM scheme is outperformed other known schemes in terms of these two metrics.